Variation of density and specific gravity of juvenile rubberwood (Hevea brasiliensis) with different height level / Ilyani Mansor - Mansor, Ilyani (2005)
The study of density and specific gravity variation was performed on Rubberwood (Hevea brasiliensis). Specific gravity was determined using the maximum moisture content method and density is known as slugs per cubic meter. The samples were examined from three different altitude of a tree - base, middle and top. The result point out that the density was highest at the base, lowest at the middle and a little increase at the top portion. While for specific gravity, the value decrease from base to top part. Hence, specific gravity is related to different height level.